Analysis and design of CMOS mixers for direct conversion receivers - Liu, Jingjing (2008)
In this project, the analysis and design of CMOS mixers for direct conversion receivers have been explored. A CMOS double-balanced Gilbert mixer operating at the centre frequency of 2.45GHz for direct conversion applications is designed using Cadence SpectreRF for the Chartered 0.18um CMOS Digital/Analog/RF process. The LO-RF leakage caused by the LO mismatch in the Gilbert mixer is examined and analyzed for three scenarios of an ideal mixer, a non-ideal mixer with parasitic effects, and an ideal mixer with LO mismatch.